Dimensions of Systemic Failure in Traditional Market Waste Management: A Scoping Review of Empirical Studies in Bandung Raya Metropolitan Area - Widarmanti, Tri; Rahayu, Agus; Adi Wibowo, Lili; Aziz Pratiwi, Nurul (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Traditional markets in Indonesia consistently rank as the second-largest contributor to national solid waste, yet the management problem remains unresolved despite over a decade of intensive empirical research. In Bandung Metropolitan Area, at least twelve empirical studies were conducted between 2014 and 2025, yet field conditions show no significant improvement, indicating systemic and multidimensional failure. This study synthesizes evidence from these twelve studies to map existing conditions, identify key actors, and analyze the gap dimensions that explain why this failure persists. This study employs a scoping review design, with reporting guided by PRISMA-ScR. Studies were identified through systematic searches conducted on Google Scholar, SINTA, Garuda, and Scopus, and the synthesis employed a three-tiered thematic analysis. The synthesis identifies five mutually reinforcing gap dimensions: a technical-operational gap (infrastructure non-compliance); a behavioral-awareness gap (low environmental literacy among vendors); a participation-incentive gap (passive participation absent behavior-changing incentives); a governance-coordination gap (fragmented multi-stakeholder operations, no permanent collaborative institutions); and an institutional-regulatory gap (persistent misalignment between regulation and operational implementation). Failures across Bandung Raya metropolitan area cannot be attributed to any single factor but to the systemic interaction of all five dimensions. These findings call for integrated and simultaneous intervention strategies and provide a roadmap for a more effective research and policy agenda.